Centralization and Decentralization in Industrial Relations - St-Laurent, Jacques (Relations industrielles / Industrial Relations, 1955)
The article reviews the book, "Centralization and Decentralization in Industrial Relations," by H. Baker and R. France. Published by the Industrial Relations Section, Princeton University (210 pages).